Vitamin A Supplementation in Extremely Low-Birth-Weight Infants: Subgroup Analysis in Small-for-Gestational-Age Infants - Londhe, Vedang A.; Nolen, Tracy L.; Das, Abhik; Higgins, Rosemary D.; Tyson, Jon E.; Oh, William; Devaskar, Sherin U.; null (American Journal of Perinatology, 2013)
Objective Preterm infants with intrauterine growth restriction are at increased risk of respiratory distress syndrome and bronchopulmonary dysplasia (BPD). A randomized clinical trial by the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Neonatal Research Network demonstrated that vitamin A supplementation in extremely low-birth-weight (ELBW) preterm infants requiring early respiratory support decreased the risk of developing BPD.Study Design A subgroup analysis of small-for-gestational-age (SGA) infants from the original NICHD trial was performed to test the hypothesis that in infants requiring early respiratory support, vitamin A supplementation decreases the relative risk of BPD or death in premature SGA infants to a greater extent than in gestational age–equivalent vitamin A–treated appropriate-for-gestational-age (AGA) infants.Results Although vitamin A supplementation significantly increased serum retinol concentrations in AGA ELBW infants (median [5th percentile, 95th percentile]: 16.3 [−7.0, 68.8] versus 2.4 [−13.9, 55.1]; p < 0.001), no increases were noted in SGA ELBW infants.Conclusions Given the limited power of this analysis due to a low number of SGA infants, these data did not provide evidence to support the hypothesis that vitamin A supplementation in preterm SGA infants requiring early respiratory support decreases the relative risk of BPD or death as compared with preterm AGA infants.
Keywords: vitamin A; IUGR—intrauterine growth restriction; BPD—bronchopulmonary dysplasia; SGA—small for gestational age; AGA—appropriate for gestational age